Avaliação do desempenho do processo de gaseificação com CO² de pellets e madeira de Pinus elliotti - Borghetti, Marcia (My University, 2022)
The gasification of biomass residues with carbon dioxide (CO2) can contribute to the production of alternative energy, obtaining by-products of commercial interest, in addition to reducing carbon emissions into the atmosphere. The densification of biomass waste brings benefits in its handling and logistics, in addition to increasing its energy density. The main objective of this work was to compare parameters of the non-condensable gas produced and the remaining solid of the gasification process in the atmosphere of CO2 of the biomass wood of Pinus elliottii (PIN 66) and residues of densified Pinus elliottii (PEL 66). For characterization tests, the biomass sample (PIN 66) presented an apparent density of 470 kg/m³ while the densified biomass sample (PEL 66) presented 1,160 kg/m3. Both biomasses presented maximum mass loss rate at 352 ºC in thermogravimetric analysis tests. The gasification tests were conducted in a fixed bed tubular reactor at a temperature of 900 ºC, using CO2 atmosphere, at different reaction times: 1.5, 10, 20, 30 and 60 minutes, with approximately 15 grams of biomass fed in each assay. The noncondensable gas produced was collected in bags of 10 and 100 L and analyzed with gas chromatography. The results showed that the total yield of non-condensable gas continuously increases with the reaction time for both samples, reaching a maximum value of 1.13 NL/g to 60 minutes of reaction for PEL 66 sample and 1.10 NL/g to 60 minutes of reaction for PIN 66 sample. The values for high heating value (HHV) were increased with the increase in reaction times reaching 6.38 MJ/Nm³ for PEL 66 and 6.50 MJ/Nm³ for PIN 66 for the 60-minute tests. The remaining solid of the tests with PEL 66 and PIN 66 indicated an evolution in conversionas the reaction time increased, reaching 95% for PEL 66 and 94% for PIN 66 in the time of 60 minutes. The evaluation of the properties of the remaining solid from Raman spectroscopy showed a higher reactivity for PIN 66 (ID/IG 1.35 and 24.6% of mesopore participation in its structure) in relation to PEL 66 (ID/IG 1.30 and 6.8% of mesopore participation in its structure), as well as a reduction in reactivity with the advancement of reaction time for both biomasses. The total pore volume reached the maximum value for PEL 66 with 30 minutes of reaction, reaching 0.4043 cm³/g and PIN 66 obtained maximum values with 20 minutes of reaction, obtaining 0.3435 g/cm³ of total pore volume. The retention of metals in the remaining solid decreased with the increase in the time of the tests, and the remaining solid of the PEL 66 sample obtained with 60 minutes of reaction presented a retention of 42.3% of Ca and 31.7% of K, and the remaining solid of the PIN 66 sample presented a retention tending to zero for Ca and 19.2% of K. The slight difference obtained for the results of non-condensable gas and in the remaining material of PEL 66 and PIN 66 biomasses indicate a promising path for the use of densified biomass residues in energy production processes. [resumo fornecido pelo autor]
A gaseificação de resíduos de biomassa com dióxido de carbono (CO2) pode contribuir com a produção de energia alternativa, obtenção de subprodutos de interesse comercial, além de reduzir as emissões de carbono na atmosfera. A densificação de resíduos de biomassa traz benefícios no seu manuseio e logística, além de aumentar sua densidade energética. O principal objetivo deste trabalho foi comparar parâmetros do gás não-condensável produzido e do sólido remanescente do processo de gaseificação em atmosfera de CO2 da madeira da biomassa de Pinus elliottii (PIN 66) e de resíduos de Pinus elliottii densificados (PEL 66). Nos ensaios de caracterização, a amostra de biomassa (PIN 66) apresentou uma densidade aparente de 470 kg/m3 e a amostra de biomassa densificada (PEL 66) apresentou 1.160 kg/m3. Ambas as biomassas apresentaram taxa máxima de perda de massa em 352 ºC nos ensaios de análise termogravimétrica. Os ensaios de gaseificação foram conduzidos em um reator tubular de leito fixo a uma temperatura de 900 ºC, utilizando atmosfera de CO2, em diferentes tempos de reação: 1,5, 10, 20, 30 e 60 minutos, com aproximadamente 15 gramas de biomassa alimentada em cada ensaio. O gás não condensável produzido foi coletado em bags de 10 e 100 L e analisado por cromatografia gasosa. Os resultados mostraram que o rendimento total de gás nãocondensável aumenta continuamente com o tempo de reação para ambas as amostras, atingindo um valor máximo de 1,13 NL/g a 60 minutos de reação para a amostra PEL 66 e de 1,10 NL/g a 60 minutos de reação para a amostra PIN 66. Os valores para poder calorífico superior (PCS) foram incrementados com o aumento nos tempos de reação chegando a 6,38 MJ/Nm³ para PEL 66 e 6,50 MJ/Nm³ para o PIN 66 para os ensaios de 60 minutos. O sólido remanescente dos ensaios com PEL 66 e PIN 66 indicou uma evolução na conversão conforme o aumento no tempo de reação, atingindo no tempo de 60 minutos 95% para o PEL 66 e 94% para o PIN 66. A avaliação das propriedades do sólido remanescente a partir da espectroscopia Raman mostrou uma reatividade maior para o PIN 66 (ID/IG 1,35 e 24,6% de participação de mesoporos em sua estrutura) em relação ao PEL 66 ((ID/IG 1,30 e 6,8% de participação de mesoporos em sua estrutura), bem como uma redução da reatividade com o avanço do tempo de reação para ambas as biomassas. O volume total de poro atingiu o valor máximo para o PEL 66 com 30 minutos de reação, atingindo 0,4043 cm³/g e o PIN 66 obteve valores máximos com 20 minutos de reação, obtendo 0,3435 g/cm³ de volume total de poros. A retenção de metais no sólido remanescente diminuiu com o aumento nos tempos dos ensaios, sendo que o sólido remanescente da amostra PEL 66 obtida com 60 minutos de reação apresentou uma retenção de 42,3% de Ca e 31,7% de K, enquanto o sólido remanescente da amostra PIN 66 apresentou uma retenção tendendo a zero para o Ca e 19,2% de K. A discreta diferença obtida nos resultados do gás não-condensável e no material remanescente das biomassas PEL 66 e PIN 66 indicam um caminho promissor para a utilização de resíduos de biomassa densificados em processos de produção de energia. [resumo fornecido pelo autor]
Keywords: Biomassa; Pinus elliottii; Dióxido de carbono; Madeira como combustível; Biomass; Slash pine; Carbon dioxide; Fuelwood